2013
DOI: 10.1007/s12032-013-0726-1
|View full text |Cite
|
Sign up to set email alerts
|

CRM1 is a novel independent prognostic factor for the poor prognosis of gastric carcinomas

Abstract: Gastric cancer (GC) is a highly aggressive malignant tumor. Its high mortality rate prompts the urgent need for novel therapeutic agents. The aim of this study is to detect the expression of CRM1 in GC, which has not been reported to date. The expression of CRM1 in GC and adjacent noncancerous tissues (ANCT) of gastrectomy specimens from 120 GC patients was measured by immunohistochemistry. In addition, correlations between the CRM1 staining and the clinicopathologic features as well as survival were analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 20 publications
2
67
0
Order By: Relevance
“…CRM1 expression is enhanced in many cancer tissues. High expression of CRM1 in gastric, ovarian, and pancreatic cancers show poor prognosis [62][63][64] . The increase in CRM1 leads to cytoplasmic abundance of tumor suppressors and cell cycle regulators, which in turn results in their aberrant activation.…”
Section: Future Perspectivementioning
confidence: 99%
“…CRM1 expression is enhanced in many cancer tissues. High expression of CRM1 in gastric, ovarian, and pancreatic cancers show poor prognosis [62][63][64] . The increase in CRM1 leads to cytoplasmic abundance of tumor suppressors and cell cycle regulators, which in turn results in their aberrant activation.…”
Section: Future Perspectivementioning
confidence: 99%
“…Furthermore, no significant differences in CRM-1 expression rate were identified between gastric carcinomas classified according to tumor type (differentiation status), although expression rates in both the nucleus and cytoplasm were higher in intestinal type gastric carcinomas than diffuse type gastric carcinomas. Zhou et al (23) reported that CRM-1 expression did not correlate with tumor differentiation status (poor vs. well to moderate). The authors also reported a higher CRM-1 expression rate in well to moderately-differentiated gastric adenocarcinomas compared with poorly-differentiated gastric adenocarcinomas (23).…”
Section: Crm-1 Expression -------------------------------------------mentioning
confidence: 99%
“…Zhou et al (23) reported that CRM-1 expression did not correlate with tumor differentiation status (poor vs. well to moderate). The authors also reported a higher CRM-1 expression rate in well to moderately-differentiated gastric adenocarcinomas compared with poorly-differentiated gastric adenocarcinomas (23). These results are consistent with those of the present study and suggest that no association exists between CRM-1 expression and tumor differentiation status in gastric carcinoma.…”
Section: Crm-1 Expression -------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of XPO1 leads to mislocalization of key regulatory proteins and is associated with resistance to chemotherapy, poor prognosis and short survival in many human malignancies [14][15][16] . XPO1 hot mutations (E571) were found in approximately 4% of primary chronic lymphocytic leukemia (CLL) patients [17,18] .…”
Section: Introductionmentioning
confidence: 99%